Rational decision making in autonomous agents - Simari, Gerardo I. (2004)
Making rational decisions is one of the key elements in the design of autonomous agents with successful behavior. Even though there have been many proposals for the support of decision making, most of them can be described either as descriptive or prescriptive. The main goal of our work is to establish the relationship between two of these models, namely bdi and mdps, in order to gain further understanding of how decisions in one model are viewed from the point of view of the other. This goal is important for the development of agent design strategies that unite the best of both worlds.